Chlorhexidine Mouthwash Use and Blood Glucose Trends by Age and Gender: Penggunaan Obat Kumur Klorheksidin dan Tren Glukosa Darah Berdasarkan Usia dan Jenis Kelamin - Dwi Wahyu Indrawati; Lely Ika Mariyati; Andika Aliviameita; Anis Khoirin Hayati; Paramitha Amelia Kusumawardani (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Oral health is intricately associated with systemic health, particularly in the aging population where chronic conditions such as diabetes are prevalent. Specific Background: Chlorhexidine 0.2% mouthwash is widely used to reduce oral microbial load, potentially influencing systemic inflammation and metabolic markers. Knowledge Gap: However, the systemic impact of routine chlorhexidine use, especially on glycemic regulation in older adults, remains insufficiently explored. Aims: This cross-sectional study aimed to evaluate the association between the use of 0.2% chlorhexidine mouthwash and random blood glucose (RBG) levels, while considering age and gender influences. Results: Among 90 respondents, predominantly aged ≥40 years (82%), 34% reported regular chlorhexidine use. Users showed a lower mean RBG (120 mg/dL) compared to non-users (128 mg/dL), though the difference was not statistically significant (p > 0.05). Gender-based analysis also revealed no significant differences. Novelty: This study contributes novel insight by highlighting a possible, albeit non-significant, trend toward improved glycemic status in chlorhexidine users. Implications: While not conclusive, these findings suggest that consistent oral hygiene via chlorhexidine may support systemic health maintenance in older adults, reinforcing the need for longitudinal studies on its metabolic effects. Highlights: Highlights a potential link between oral hygiene and blood glucose control. Shows lower average glucose in chlorhexidine users, though not significant. Supports further research on systemic benefits of mouthwash use in elderly. Keywords: Chlorhexidine 0.2%, Blood Glucose, Oral Health, Aging Population, Cross-Sectional Study